Analysis of methods and algorithms for remote photoplethysmography signal diagnostic and filtering - Berezhnyi, Ihor; Nakonechnyi, Adrian (Видавництво Львівської політехніки, 2024)
Remote photoplethysmography is becoming increasingly common in telemedicine for non-invasive physiological monitoring of the cardiovascular system. However, signal reliability has been reduced due to noise and artifacts, which requires reliable diagnostic and filtering methods. The research aim is to evaluate existing methods and algorithms for diagnosing and filtering remote photoplethysmography signals to improve the accuracy of human cardiovascular monitoring. A systematic review has identified methodologies for improving remote photoplethysmography signals by analyzing their principles, implementation, and effectiveness. Various approaches have been analyzed, including the use of statistical computing, adaptive filters, and machine learning algorithms. Each approach offers unique advantages and limitations in terms of noise reduction and artifact removal.
Keywords: Filtering; Photoplethysmography; Heart rate variability; Wavelet transform